Synthesis of Reduced Graphene Oxide and Zinc Oxide Composite From Candlenut Shell Charcoal (Aleuritas moluccana) - Asri Saleh; Fadhil Asy’ari Amhadin; Iin Novianty (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Candlenut shell is one of the by-products of the hazelnut processing industry which has not been widely utilized. However, the carbon content from the candlenut shell can be used as charcoal, which has the potential as the base material for making reduced graphene oxide (GO) capacitance products. After the composite process, characterization of the rGO and its composites was carried out with FTIR and XRD instruments. The synthesis results obtained are combined with ZnO to determine the value of the electrical result. From FTIR characterization, it was found that C=C, C-O, and O-H functional groups were formed, and the XRD measurement resulted in a peak diffractogram at 2θ ⁓ 23,96°, which is typical for rGO material. The result of testing with a conductivity meter at a rGO-ZnO 0:1 ratio, produced a capacitance value of 4,72 mF, in terms of 1:2, 6,34 mF; 1:1, 7,36 mF; 2:1, 5,18 mF; and 1:0, 4,28 mF. The optimum ratio of rGO-ZnO with the highest capacitance value was found, which is the ratio of 1:1 with a capacitance value of 7,36 mF.Abstrak: Tempurung kemiri merupakan salah satu hasil samping dari industri pengolahan kemiri yang masih belum banyak dimanfaatkan secara luas. Akan tetapi kandungan karbon pada tempurung kemiri dapat dijadikan arang yang berpotensi sebagai salah satu bahan dasar pembuatan Grafena Oksida(GO) tereduksi. Hasil sintesis yang didapatkan dikompositkan dengan ZnO untuk mengetahui nilai kapasitansi yang dihasilkan. Setelah proses komposit, dilakukan karakterisasi terhadap rGO dan kompositnya dengan instrumen FTIR dan XRD kemudian diuji nilai kapasitansi elektrik yang dihasilkan dengan alat multimeter. Berdasarkan hasil karakterisasi FTIR, didapati terbentuk gugus C=C, C-O, O-H dan uji XRD menghasilkan nilai 2θ ⁓ 23,96o yang mengindikasikan rGO .Hasil pengujian dengan konduktimeter menghasilkan data perbandingan rGO-ZnO 0:1 menghasilkan nilai kapasitansi 4,72 mF, 1:2, 6,34 mF; 1:1, 7,36 mF; 2:1, 5,18 mF; dan 1:0, 4,28 mF. Diperoleh perbandingan optimum rGO-ZnO dengan nilai kapasitansi paling besar yaitu perbandingan 1:1 sebesar 7,36 mF.